2021
DOI: 10.11594/ijmaber.02.08.07
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Challenges Facing Teenage Mothers in School and How They Cope in the Wa West District

Abstract: Education is a built-in mechanism that retains its essential value as a human right, not as a static commodity to be viewed in isolation from its larger context. Every person has the right to quality education and the ability to guarantee their human rights are secure for the long term. This research examined teenage mothers' struggles in school. The study employed a descriptive phenomenological approach. Twelve teenage mothers were selected, using a snowball sampling approach. Semi-structured interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The challenges associated with teenage motherhood were (1) pregnancy discomfort, (2) educational challenges, and (3) financial issues. This claim was supported by Adangabe et al (2021), who found that teenage mothers enrolled in a new normal setting of education with different learning modalities during the pandemic faced several challenges, including a lack of financial support, poor time management, low self-esteem, and emotional instability. Table 5 displays the coping mechanisms of teenage mothers for this transition.…”
Section: Financial Issuesmentioning
confidence: 94%
“…The challenges associated with teenage motherhood were (1) pregnancy discomfort, (2) educational challenges, and (3) financial issues. This claim was supported by Adangabe et al (2021), who found that teenage mothers enrolled in a new normal setting of education with different learning modalities during the pandemic faced several challenges, including a lack of financial support, poor time management, low self-esteem, and emotional instability. Table 5 displays the coping mechanisms of teenage mothers for this transition.…”
Section: Financial Issuesmentioning
confidence: 94%
“…These concerns are the problems that adolescent mothers encounter as they strive to reconnect their roles as students and mothers. With the struggling obligations of motherhood and society's negative judgment, these young mothers are usually traumatized by the people, which causes emotional wounds (Adangabe et al, 2021).…”
Section: Young Mothers' Experiences In Early Parenthoodmentioning
confidence: 99%
“…These young mothers had to face a hostile environment where they felt separated, humiliated, and stigmatized. Without emotional reinforcement, teenage mothers may encounter anxiety and rage, while others may encounter depression due to society's shame culture (Adangabe et al, 2021). Jones et al (2019) reported that young mothers frequently experienced discrimination from society through dislike, negative criticism, and deliberative encounters.…”
Section: Young Mothers' Experiences In Early Parenthoodmentioning
confidence: 99%
See 1 more Smart Citation